Larangan Pengunggahan Konten Terkait FPI: Tinjauan Perspektif Hak Asasi Manusia di Indonesia - Muhammad Fauzi; Mellayanah Mellayanah; Muhammad Akmal Rizki Rivaldi; Fairuz Arta Abhipraya (Universitas Muhammadiyah Purwokerto, 2021)
The release of decisions with Home Ministers, Ministers of Law and Human Rights, Ministers of Communications and Informatics, Attorney General, The Police Chief of the Republic of Indonesia (Kapolri) and the Head of the National Body of Counter-Terrorism has been the basis for the dissolution and banning of all activities of the Islamic Defenders Front (FPI). Following up on this, it issued a declaration of Maklumat Kapolri No. 1/Mak/I/2021 on compliance with the ban on activities, the use of symbols and attributes and the application of fpi activities. Articel 2d of the maklumat forbidding access, uploading, and disseminating content related to FPI via the Internet is considered to have limited human rights. The study aims to see if there are any infractions and irregularities within the human rights code of the FPI content in the declaration. As for the research method used was normative juridical with a legal and conceptual approach. The source of data used is legislation on human rights, books, articles, and other sources related to the study. It was found in the study that article 2d of the maklumat went beyond the human rights code based on the principles of siracusa and the testing of three sets (three part test). Not only that, article 2d of the maklumat also threatens the freedom of press from journalists and the media in charge of spreading information to the public. The advice of the author regarding this matter should be the chief of police to update the declaration according to the purpose and purpose of the declaration issued, or at least revoke article 2d of the maklumat that feels has restricted the special human rights of free expression. This is so that the entire legal action in this country is consistent with the principles of the state of law and human rights.Keywords: human rights, freedom of expression, freedom of pers